2009
DOI: 10.1080/17461390903009141
|View full text |Cite
|
Sign up to set email alerts
|

Golf‐related injuries: A systematic review

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Cabri, J., Sousa, J. P., Kots, M., Barreiros, J. (2009) Abstract.A review was completed to study the prevalence of musculoskeletal injuries in golf and to stimulate the discussion on possible injury mechanisms. The main conclusion of most published studies is that, although professional and amateur golfers show similar anatomical distribution of injuries by body segment, differences tend to be present in the ranking of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 60 publications
1
74
0
Order By: Relevance
“…Due to increased participation, golf-related injuries are increasing, also. Cabri et al (2009) indicated that golf players experienced injuries, resulting from overuse or from traumatic cause. However, health benefits and golf practice-related risks have not been fully explored.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to increased participation, golf-related injuries are increasing, also. Cabri et al (2009) indicated that golf players experienced injuries, resulting from overuse or from traumatic cause. However, health benefits and golf practice-related risks have not been fully explored.…”
Section: Introductionmentioning
confidence: 98%
“…However, health benefits and golf practice-related risks have not been fully explored. Furthermore, controversy still exists in the literature (Cabri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the golfer is to place a ball inside a small hole with the least hits possible (Hume et al, 2005). Although it is not considered an intensive and exhausting sport, skeletal-muscle stress and demand are associated with high injury incidence (Cabri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…LBP has been implicated as the major complaint of golfers as well as the body region associated with a larger incidence of injuries (Cabri et al, 2009;Lindsay et al, 2002;McHardy et al, 2007). This led to a growing interest in quantifying the factors that can be influenced by LBP (Gluck et al, 2008;Vad, 2004), as the e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The two main factors associated with changes in the golf swing are the handicap (Hc) and the incidence of low back pain (LBP) (Cabri et al, 2009;Lindsay et al, 2000). Lindsay et al (2000) stated that more than 70% of golf players experienced injuries resulting in playing at an unsatisfactory skill level during a short period of time.…”
Section: Introductionmentioning
confidence: 99%